Pengaruh Edukasi Gizi Dengan Logbook Terhadap Pengetahuan Dan Asupan Remaja Putri Anemia - Aolian Asrori; Abdul Salam; Irianto Irianto; Lalu Khairul Abdi (Jurnal Gizi Prima (Prime Nutrition Journal), 2020)
Background : Anemia is an unresolved nutritional problem in Indonesia. Data from the Babakan Health Center reported that 19.1% of adolescent girls at SMPN 5 Mataram had anemia, while according to WHO the acceptable threshold was <5%. One of the causes is the lack of knowledge about anemia, low adherence to taking blood booster supplements and there is no media to monitor the intake and adherence. Objectives : The purpose of this study was to analyze "The effect of nutrition education using anti-anemia logbooks on the knowledge and nutritional intake of anemic adolescent girls at SMPN 5 Mataram". Methods : Type of research is an analytical experiment with a quasi-experimental design using a non equivalent and non rendomized control group pretest posttest design. Population: all grade VIII anemia adolescent girls at SMPN 5 Mataram totaling 30 people and a sample of 28 people who were divided into experimental and control groups. Results : In the knowledge variable, there was a significant effect on the group using the logbook and the group without the logbook and the increase was significantly different between the two groups with p = 0.034. In the intake variable, providing education with the Anti Anemia Logbook (Go Mia) had a significant effect on energy and protein consumption with a p value of <0.05, however, the group that did not use the logbook (control group) did not show a significant effect, as did intake. Fe did not show a significant effect in either the experimental group or the control group. Conclusion : Nutrition education using logbook is effective to increase knowledge, energy and protein intake but not effective to increase iron intake.